2019
DOI: 10.1653/024.102.0308
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cherry Cultivar and Trapping Height on Population Dynamics of Drosophila Fruit Flies in Cherry Orchards in Northern China

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(11 reference statements)
0
0
0
Order By: Relevance
“…It is important to remark, though, that our findings suggest that the height position of the bait spray could play a role in its effectiveness. It has also been shown that height played a role in trap efficacy in field conditions, where traps suspended at 1 to 1.5 m above the soil captured the highest rate of D. suzukii compared to traps located at ground level and 2 m above the soil [35].…”
Section: Discussionmentioning
confidence: 96%
“…It is important to remark, though, that our findings suggest that the height position of the bait spray could play a role in its effectiveness. It has also been shown that height played a role in trap efficacy in field conditions, where traps suspended at 1 to 1.5 m above the soil captured the highest rate of D. suzukii compared to traps located at ground level and 2 m above the soil [35].…”
Section: Discussionmentioning
confidence: 96%
“…It is important to remark, though, that our findings suggest that the height position of the bait spray could play a role in its effectiveness. It has also been shown that height played a role in trap efficacy in field conditions, where traps suspended at 1 to 1.5 m above the soil captured the highest rate of D. suzukii compared to traps located at ground level and 2 m above the soil (Man et al, 2019).…”
Section: Discussionmentioning
confidence: 96%